RESEARCH AND DEVELOPMENT (R&D) METHOD AS A MODEL DESIGN IN EDUCATIONAL RESEARCH AND ITS ALTERNATIVES - Sri Gustiani (Politeknik Negeri Sriwijaya, 2019)
The growth of educational research as one of scientific research has come to the state where the researchers in this field make their studies to generate a model for better educational practices. One of the most outstanding model designs is Research and Development (R&D) Method by Borg & Gall (1983), nevertheless, the widely use of this method prompts a question whether it is the only proper method in educational research. This paper is aimed to discuss in depth the R&D Method in some educational research by comparing the simplified steps and characteristics in those research. This paper also provides some alternatives of model design for educational research in which the usage and its implementation are adjusted in accordance to the research context and researchers characteristics.